Empowering women via social safety nets and service delivery - Arshad, Rozita (2013)
Social safety Nets (SSNs) are the form of government intervention to assist the “needy” groups including the single mothers.SSNs should be established as a mechanism that can be used to alleviate poverty, especially among single mothers. However, the barrier that restricts SSNs as mechanism to improve the quality of life for single mothers is a failure of service delivery functions. The single mothers can be empowered through good delivery system of SSNs because it can support their social development. Basically, SSNs is used as short term supporting system to generate independent nature of life and consciousness among women (single mothers).Thus this study aims to explore how the delivery of SSNs services or assistance to single mothers operates and whether SSNs empowered them.